Compressive behavior and design method of BFRP bars constrained with a BFRP spiral with different spacings in concrete members. (1st October 2022) - Tang, Yu; Sun, Zeyang; Wei, Yang; Zou, Xingxing
Highlights: The compressive strength of BFRP bars embedded in concrete structures could be lower than those compressed as a single rod. Sufficient confinement could restrict the lateral deformation of the BFRP bars, and postpone their compressive failure. The compressive modulus of the BFRP bars is proved to be identical to their tensile modulus. The accuracy of most compressive capacity equations for FRP-RC columns decreases with increase of their stirrup spacing. A new design equation is established in this paper for approaching the compressive capacity of BFRP-RC columns. Abstract: This paper provides an experimental study on the compressive behavior and design method of BFRP bars constrained with a BFRP spiral with different spacings in concrete columns. Thirty columns reinforced with different BFRP bars and BFRP spirals with different spacings were designed and tested under concentric compression. The results show that the compressive modulus of the BFRP bars was identical to their tensile modulus. Reducing the spiral spacing could effectively restrict the lateral deformation of the longitudinal BFRP bars and hence postpone their compressive failure and improve their compressive strength in concrete structures. The service environment of the concrete structures could further decrease the in-place compressive strength of the BFRP bars. The accuracy of most existing design equations (for predicting the compressive capacity of FRP-RC columns) significantly decreases with increasing spiral spacing. Based on these findings, a new approaching method was proposed to evaluate the compressive strength of FRP-RC columns by considering the actual compressive contribution of the longitudinal FRP bars and the strength reduction of the confined concrete. A promising prediction accuracy was preliminarily obtained for the proposed equation through verification with the test results.